Evaluating the financial performance of the socially responsible investment under the bull and the bear market conditions - Liu, Jinxin (2011)
This research is dedicated to detect the effects of the market conditions on the performance of the socially responsible investment. Using the Lunde-Timmermann scheme, the sample period, which is set between February 2002 and June 2011, is classified into period of bull market and period of bear market. Sharpe ratio, Jensen‟s alpha and Treynor‟s ration are employed to compare the performance of the SRI unit trusts and the non-SRI unit trusts in the United Kingdom. Statistically significant differences are found in the bull market supporting that the SRI unit trusts outperform the non-SRI ones. And in the bear market, the SRI unit trusts tend to underperform their non-SRI counterparties. It can be inferred that the different coverage of bull and bear market period is an important factor for the diversity of the previous research results. Analysis of previous researches that covers the UK market generates some proof of the inference of this research.